2016
DOI: 10.1007/s00418-016-1470-3
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Cav2.1 channels and calcium ions in nerve terminals following end-to-side neurorrhaphy: ionic imaging analysis by TOF–SIMS

Abstract: The P/Q-type voltage-dependent calcium channel (Cav2.1) in the presynaptic membranes of motor nerve terminals plays an important role in regulating Ca transport, resulting in transmitter release within the nervous system. The recovery of Ca-dependent signal transduction on motor end plates (MEPs) and innervated muscle may directly reflect nerve regeneration following peripheral nerve injury. Although the functional significance of calcium channels and the levels of Ca signalling in nerve regeneration are well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Jiang H et al demonstrated NanoSIMS imaging, which makes it possible to visualize neutral lipids in cytosolic lipid droplets in intestinal enterocytes, chylomicrones at the basolateral surface of enterocytes, and lipid droplets in cardiomyocytes and adipocytes 28) . In addition, Liu CH et al have shown a new approach to calcium ion imaging using TOF-SIMS 29) . These approaches might be useful for visualizing intra-myocellular lipids in the future.…”
Section: Methodological Improvement For High-sensitivity and High-resmentioning
confidence: 99%
“…Jiang H et al demonstrated NanoSIMS imaging, which makes it possible to visualize neutral lipids in cytosolic lipid droplets in intestinal enterocytes, chylomicrones at the basolateral surface of enterocytes, and lipid droplets in cardiomyocytes and adipocytes 28) . In addition, Liu CH et al have shown a new approach to calcium ion imaging using TOF-SIMS 29) . These approaches might be useful for visualizing intra-myocellular lipids in the future.…”
Section: Methodological Improvement For High-sensitivity and High-resmentioning
confidence: 99%